Predictors of nutritional status and fluid balance among ESRD patients undergoing hemodialysis - Afriyanti, Esi; Krisdianto, Boby Febri; Transyah, Chichi Hafifa (Jurnal Ners, 2025)
Introduction: Patients with End-Stage Renal Disease (ESRD) undergoing hemodialysis must accommodate significant lifestyle modifications, emphasizing nutritional management and fluid restriction, to realize optimal therapeutic outcomes due to the stringent adherence required by the treatment. Deviations from adherence can precipitate complications, compromising the clinical status of patients. Methods: This study employed a quantitative, correlational, and cross-sectional methodology to evaluate 245 ESRD patients undergoing hemodialysis who met the inclusion criteria. Data were acquired utilizing a multistage sampling technique, incorporating proportional random and consecutive sampling, and employing questionnaires addressing knowledge, family support, and perception (B-IPQ). Results: The participants' average age was 51.37±11.804 years, with males representing 60% (147 individuals) of the sample. A significant 81.6% (200 participants) demonstrated proficient knowledge levels. Family support was assessed as satisfactory for 90.6% (222 participants), and 82% (201 participants) exhibited positive perceptions. The analysis identified a significant correlation between Duration of Illness and IDWG (p<0.05), evidenced by a Pearson's correlation coefficient (r) of 0.153. A noteworthy inverse relationship between knowledge levels and Ureum (p<0.05) was also observed. Conclusions: The findings suggest a correlation between knowledge and nutritional management, particularly regarding urea levels, while the duration of hemodialysis is correlated with IDWG. Conversely, factors related to family support did not demonstrate a significant correlation with aspects of nutrition and fluid management, such as urea, creatinine, Hb, sodium, and potassium.